Exogenous organic acids promoted phytoremediation by Hydrangea macrophylla in cadmium‑contaminated soil - Yunjing Song; Qian Cheng; Bing Zhao (Ecotoxicology and Environmental Safety)
Cadmium (Cd) contaminants with high toxicity and mobility seriously threatens the ecological environment and human safety. Hydrangea macrophylla is a potential plant for Cd-contaminated soil remediation. Exogenous organic acids have been proven to effectively enhance the phytoremediation of soil contaminated with Cd. However, research on the effects of organic acids on Cd tolerance and accumulation of H. macrophylla remains scarce. In this study, a potted experiment was performed with H. macrophylla as the research object. The effects of acetic acid (AA), citric acid (CA), and malic acid (MA) with different concentrations (2.5, 5, and 10 mmol·kg−1) on the growth physiology, Cd absorption and accumulation of H. macrophylla and soil microecological environment under Cd stress were systematically studied. Results indicated that organic acids increased chlorophyll content and promoted the growth of H. macrophylla, the biomass of shoots and roots increased by 165.44 % , 161.50 % under 5 mmol·kg−1 citric acid treatment. Furthermore, organic acids reduced the level of membrane lipid peroxidation in leaves, increased plant biomass and promoted root growth of H. macrophylla. By boosting superoxide dismutase (SOD), peroxidase (POD), and catalase activities (CAT), elevating levels of proline (Pro), non-protein thiol (NPT), glutathione (GSH) and phytochelatins (PCs), exogenous organic acids promoted the Cd tolerance of H. macrophylla. In particular, 5 mmol·kg−1 CA had the best effect on improving the Cd tolerance of H. macrophylla. The roots of H. macrophylla accumulated a large amount of Cd, ranging from 365.04 to1111.67 μg·plant−1. Appropriate concentration of organic acids increased the total Cd accumulation by 1.12–2.07 times of H. macrophylla. The translocation factor (TF) increased by 97.91 %, 107.95 % under 5 mmol·kg−1 CA and 10 mmol·kg−1 MA treatments. Nevertheless, TF values were all less than 1. We posit that using H. macrophylla and organic acids could reduce the Cd bioavailability in the soil mainly through rhizosphere immobilization and plant absorption. Additionally, organic acids increased the soil pH, accompanied by changes in soil enzyme activities. 10 mmol·kg−1AA and MA reduced the available Cd concentration by 20.42 % and 31.65 %, respectively. Overall, exogenous organic acids can assist H. macrophylla in phytoremediation. 5 mmol·kg−1 CA treatment was considered the best choice for the remediation of heavy Cd-contaminated soil by H. macrophylla.